PP53 Applying The VALIDATE Approach To Frame The Assessment Of Integrated Care Management In Aortic Valve Stenosis. (23rd December 2022) - Valls-Comamala, Victòria; Fernandez-Barceló, Carla; Trilla, Marc; Vidal, Barbara; Sitges, Marta; Sampietro-Colom, Laura
Abstract : Introduction: The assessment of current technologies needs a more holistic approach to obtain accurate recommendations for decision-making. The VALues In Doing Assessments of health TEchnologies (VALIDATE) methodology considers that facts and values from all stakeholders need to be included in the scoping of an assessment to gather the comprehensive information needed for unbiased decision-making. This report aimed to explore how to properly assess the integrated care of patients with aortic valve stenosis (AVS) using the VALIDATE approach. Methods: A literature review was conducted, and 11 semi-structured interviews were performed with various hospital-based healthcare professionals (cardiac surgeon, clinical cardiologist, interventional cardiologist, anesthetist, process coordinator nurse, and others) and patients. Content analysis was used for data analysis and integration. Results: The literature review showed that the cardiology and cardiac surgery perspectives were dominant in 90 percent of the articles and present in the remaining ten percent. The perspectives of other specialties (anesthesiology, primary care, and psychology) were included in three percent of the articles and patient perspectives were included in nine percent. Interviewing and considering the perspectives of the different stakeholders involved in the care pathway identified the following indicators that should be included in the assessment care for patients with AVS: difficulties associated with late diagnosis of AVS; the need to incorporate a multidisciplinary approach in patient risk assessment; the importance of geriatric evaluations; considering patient (and family and caregiver) preferences for type of treatment; the importance of following up pharmaceutical treatment and palliative care; use of telemonitoring; and digital exclusion of patients with respect to the use of apps for prehabilitation and rehabilitation. Conclusions: The stakeholders interviewed were involved in different steps of the care pathway and had differing needs, some of which were not found in the literature. The indicators suggested for inclusion in the assessment differed according to type of stakeholder and their involvement in the care pathway. Therefore, this case study exemplifies the VALIDATE method and endorses the need for multistakeholder involvement in eliciting values when scoping the assessment of a complex technology.